Effect of Company Size, Leverage, profitability, scope of company operations, and Iso 14001 certification on the quality of environmental disclosure - Yuliana, Vita Aprilia; Kusumawati, Eny (Dinasti Publisher, 2024)
Quality of environmental disclosure is the disclosure made by a company regarding its obligations to the environment. This research aims to analyze the influence of company size, leverage, profitability, company operational coverage, and ISO 14001 certification on the quality of environmental disclosure in non-financial companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used in this research was purposive sampling. A total of 163 companies have met the criteria as observation units. The analytical method used is multiple linear regression analysis. The research results provide empirical evidence that company size and profitability have effect the quality of environmental disclosure. Meanwhile, leverage, company operational coverage, and ISO 14001 certification have no effect on the quality of environmental disclosure.